Electron transfer dominated triboelectrification at the hydrophobic/slippery substrate—water interfaces - Yi Chen; Xiaojuan Li; Chenggong Xu; Daoai Wang; Jinxia Huang; Zhiguang Guo; Weimin Liu (Friction)
Abstract Triboelectric nanogenerator (TENG) based on triboelectrification has attracted wide attention due to its effective utilization of green energy sources such as marine energy. However, researches about liquid-liquid triboelectrification are still scanty as solid—liquid triboelectrification has been widely studied. Herein, this work focuses on the hydrophobic/slippery substrate—water interfacial triboelectrification based on the solid friction materials of polytetrafluoroethylene (PTFE) nanoparticles. The hydrophobic/slippery substrate—water interfacial triboelectrification are studied by assembling PTFE coated Al sheets and perfluoropolyether (PFPE) infused PTFE coated Al sheets (formed the slippery lubricant-infused surfaces (SLIPSs)) as the friction electrode, and water as liquid friction materials, respectively. The results show that the hydrophobic TENG output performances improved as the PTFE nanoparticles cumulating, and the SLIPSs TENG output performances increased with the thinner PFPE thickness. Both the triboelectrification behavior of hydrophobic/SLIPSs TENG assembled in this work are dominated by the electron transfer. Thanks to the introduction of SLIPSs, the SLIPSs TENG exhibits superior stability and durability than the hydrophobic TENG. The investigation of hydrophobic/slippery substrate—water interfacial triboelectrification contributes to optimize the TENG performances, and expands the application in harsh environments including low temperature and high humidity on the ocean.